Neural Implants Without Active Implanted Electronics: Possibilities and Limitations of Transcutaneous Coupling in Miniaturized Active Implants - Patrick Kiele; Gregor Laengle; Martin Schmoll; Cristian Pasluosta; Ronny Pfeifer; Martin Schuettler; Oskar Aszmann; Thomas Stieglitz (IEEE Open Journal of Engineering in Medicine and Biology, 2025)
Goal: Transcutaneous coupling scheme for wireless powering and signal in active implants are known for more than a decade. This study aimed to investigate the in vivo behavior of this approach to drive multiple channels of an implanted peripheral nerve interfaces. Methods: The stimulation signals were transmitted through the skin over two contacts to an intracorporeal counterpart which was connected to a cuff electrode with two channels. EMG after stimulation was measured to establish recruitment curves. Results: Limitations of transcutaneous coupling were found in the feasible complexity of the system. High electrical crosstalk in a multi-channel system reduces this approach to low channel applications, such as pain treatment. No significant influence of the pulse width or extracorporeal stimulation amplitude on the electrical crosstalk was observed. Conclusions: The study's findings provide insight into the behavior of the transcutaneous coupling scheme in vivo and highlight the limitations and areas of application. Our results indicate that transcutaneous coupling schemes are a promising alternative approach for wireless powering of implants, as it does not require complex implanted electronics, expensive sophisticated electronics, and hermetic enclosures. Physical constraints, however, limit the use in highly selective nerve stimulation scenarios.